Compared biology of Tetranychus urticae in cotton cultivars I. Biological cycle - Silva, Marineide de Andrade; Parra, José Roberto Postali; Chiavegato, Luiz Gonzaga (Pesquisa Agropecuaria Brasileira, 2014)
A laboratory study was carried out on the biology of Tetranychus urticae (Koch 1836) (Acari: Tetranychidae) in cotton cultivars IAC-17, IAC-18 and IAC-19, with the objective of assessing the behavior of this spider mite. The study was carried out in leaf disks, under the following environmental conditions: temperature ranging from 24°C to 26°C, air relative humidity ranging from 52% to 62% and 14 hours photoperiod. Under these conditions, the cotton cultivars did not exert any influence on the duration of the immature phases and of the preovipositional period of T. urticae. as well as on its egg-laying capacity. Cultivar IAC-19 was the least adequate for the mite, since it provided the smaller values for viability in the egg to adult stage, duration of the egg-laying period and femals longevity. For all cultivars, the average duration of the quiescent period in the deutonymph phase was greater than that of the active period.